Dimensions of structural developments in the solidarity based economy: an analysis of the states Bahia and Paraná - Silva, Sandro Pereira; Nagem, Fernanda Abreu (Revista Econômica do Nordeste, 2016)
This paper aims to analyze the current context of structural challenges and the potential of solidaritybased economy enterprises (SEE). As the empirical object, the data used was obtained by the Mapping of the Solidarity Based Economy in Brazil focusing on the organization of SBEE in the states of Paraná and Bahia. In general, one can conceptualize the solidarity based economy as a set of initiatives for economic and community aims that are organized through the perspective of collective self-managed work, which somehow finds ways to transcend this democracy to other spheres of social life beyond the solely economic. Overall, it was noticed that although there are some special features in the totality of SBEE in each of these states, they face similar structural difficulties that do not differ in other Brazilian states.